PENGAWASAN PEMUNGUTAN PAJAK RESTORAN OLEH BADAN PENDAPATAN DAERAH KOTA PEKANBARU - Gesya Ramadhani; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Restaurants are increasingly growing in Pekanbaru City. The restaurant is a place to eat food and drinks provided with chargeable. The restaurant have adequate tax potential should be able to increase the local revenue from the tax sector ie restaurant tax. The occurrence of problems such as the number of dishonest restaurants reported taxes and the gap between the target and the realization, of course can not be separated from the supervision of the regional income agency in terms of tax revenue restaurant.The concept of the theory that researchers use is Management, Supervision, and Tax. This research type is qualitative research with descriptive method. Selection of informants of this study using the technique "purposive sampling", which this informant is predetermined and the determination of informants based on the consideration that the selected informant is the people who know and involved. Data collection techniques through interviews, documentation, and observation.The results of this study, Supervision of Restaurant Tax Collection by Pekanbaru City Revenue Board considered not maximal. By looking at the number of restaurants that violate the contents of the provisions of Regional Regulation No. 6 of 2011 on Restaurant Tax. Factors affecting the Supervision of Restaurant Tax Collection by Pekanbaru City Revenue Board are lack of human resources, inadequate infrastructure, lack of awareness of restaurant owner affecting the supervision of restaurant tax collection in Pekanbaru City.Keyword : Supervision, Tax, Restaurant